Analisis Kinerja Proteksi Petir Pada Saluran Transmisi Tenaga Listrik Menggunakan Pemrograman Python - Rofi Hariadi; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
One of main causes of interruption of electrical power supply is the lightning strike on overhead power transmission lines. The lightning performance of transmission line can be determined by value of shielding failure flashover rate (SFFOR) and back flashover rate (BFOR). The object of this study is to create a computer application to compute lightning performance on the transmission lines using Python programming. Pythons package tkinter used for program interface window. Application programming is done by using the concept of Object Oriented Programming (OOP) using Pythons keyword class. Validation shows that the application has applied the method correctly with a percentage error 0 % for SFFOR and 0,344 % for BFOR. The application can do analysis on the factors that affecting SFFOR and BFOR such as the effect of thunder day, tower foot resistance, and number of isolator disks. The results obtained in this study is computer application that can perform lightning performance analysis and analysis of factors that can affect it, such as thunder day, tower foot resistance and the number of isolator disks. Keywords: BFOR, lightning performance, OOP, overhead transmission line, Python, SFFOR, tkinter